Inoculation of Bacillus subtilis in acidic soil amended with biochar and liming materials in maize cultivation - Diaz Chuquizuta, Henry (2025)
The use of amendments in combination with Bacillus subtilis has been understudied as a strategy for rehabilitating acid soils and improving cropping systems. This study aimed to evaluate the effects of amendments and B. subtilis on the development, yield, and nutritional quality of the hard yellow maize Marginal 28 T variety. A randomized complete block design with a factorial arrangement was employed, considering five amendments, including biochar, alongside the application of B. subtilis. The combination of biochar and B. subtilis significantly increased plant and ear height (p < 0.01), achieved a grain yield of 4.11 t ha⁻¹, and reduced flowering time by seven days. Strong correlations were observed between male and female flowering (r = 0.99) and between stem diameter and leaf area (r = 0.95), indicating improved vegetative development. Soil pH and nutrient availability, such as phosphorus, were also enhanced. The combined use of amendments and B. subtilis optimizes yield and improves soil chemical properties. Thus, applying biochar and B. subtilis improves growth, yield, and soil quality, consolidating a promising strategy for sustainable agriculture in acid soils.